Evaluation of different media for the production of cephalosporins by Streptomyces clavuligerus ATCC 27064 - Antonio, Tatiana [UNESP]; Bellão, Carolina; Corrêa, Tatiana [UNESP]; Cavallieri, André Pastrelo [UNESP]; Badino, Alberto Colli; Araujo, Maria Lucia Gonsales da Costa [UNESP] (Brazilian Archives of Biology and Technology, 2012)
The aim of this work was to compare the composition of a complex and soluble culture medium to eight other media described in the literature through the batch cultivation in a conventional bench-scale bioreactor for the production of cephamycin C by a wild strain of Streptomyces clavuligerus. The proposed medium resulted in an antibiotic production 1.5 to 7.5 times higher than the other culture media.
Keywords: β-lactam antibiotic; Streptomyces clavuligerus; lysine metabolism; complex medium